2023
DOI: 10.1172/jci.insight.157191
|View full text |Cite
|
Sign up to set email alerts
|

Boosting peripheral BDNF rescues impaired in vivo axonal transport in CMT2D mice

Abstract: Gain-of-function mutations in the housekeeping gene GARS1, which lead to the expression of toxic versions of glycyl-tRNA synthetase (GlyRS), cause the selective motor and sensory pathology characterising Charcot-Marie-Tooth disease (CMT). Aberrant interactions between GlyRS mutants and different proteins, including neurotrophin receptor TrkB, underlie CMT type 2D (CMT2D); however, our pathomechanistic understanding of this untreatable peripheral neuropathy remains incomplete. Through intravital imaging of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 94 publications
1
36
1
Order By: Relevance
“…Disturbances in axonal transport have been identified in models of many different forms of both genetic and acquired peripheral neuropathy (74)(75)(76), including cellular and in vivo models of CMT2D (27,42,77,78); however, whether these deficits are a primary cause of disease or simply a secondary consequence of neuropathology remains an open question. While we have not determined whether impaired endosome trafficking is a driver of neuropathy in Yars E196K mice, we do provide the first evidence for its dysfunction in DI-CMTC and only the second study in which axonal transport has been identified as being impaired in mammalian peripheral neuropathy in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Disturbances in axonal transport have been identified in models of many different forms of both genetic and acquired peripheral neuropathy (74)(75)(76), including cellular and in vivo models of CMT2D (27,42,77,78); however, whether these deficits are a primary cause of disease or simply a secondary consequence of neuropathology remains an open question. While we have not determined whether impaired endosome trafficking is a driver of neuropathy in Yars E196K mice, we do provide the first evidence for its dysfunction in DI-CMTC and only the second study in which axonal transport has been identified as being impaired in mammalian peripheral neuropathy in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Sciatic nerves and tibialis anterior muscles were dissected from PBS-perfused and non-perfused mice. Proteins were extracted from NSC-34 cells and tissues, and evaluated by western blotting as detailed previously (42). Primary and secondary antibodies used for western blotting are detailed in Table S2 and Table S3, respectively.…”
Section: Protein Extraction and Western Blottingmentioning
confidence: 99%
See 3 more Smart Citations